2006
DOI: 10.1007/s10964-006-9152-4
|View full text |Cite
|
Sign up to set email alerts
|

Academic Achievement and Problem Behaviors among Asian Pacific Islander American Adolescents

Abstract: Using data from the National Longitudinal Study of Adolescent Health, this study tests whether the relationship between academic achievement and problem behaviors is the same across racial and ethnic groups. Some have suggested that academic achievement may be a weaker predictor of problem behaviors among Asian Pacific Islander American (API) youth; that they can have high grades but still exhibit problem behaviors. This study finds that academic performance is a significant predictor of aggressive and nonaggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 35 publications
2
32
1
1
Order By: Relevance
“…Therefore, and in agreement with previous findings (Bachman et al, 2007;Choi, 2007), it seems that the substances were more likely to be used by adolescents who were not doing well in school (and vice versa).…”
Section: Scholastic and Sport Factors And The Relation To Substance Usupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, and in agreement with previous findings (Bachman et al, 2007;Choi, 2007), it seems that the substances were more likely to be used by adolescents who were not doing well in school (and vice versa).…”
Section: Scholastic and Sport Factors And The Relation To Substance Usupporting
confidence: 92%
“…Adolescent substance abuse 1 and misuse (SUM) is a major public health problem in the world today, and often creates certain difficulties for individuals who are misusing substances, their parents and families, school, peers, and society as a whole (Bezinovic & Malatestinic, 2009;Choi, 2007;Golder, Gillmore, Spieker, & Morrison, 2005;Haller, Handley, Chassin, & Bountress, 2010;Raboteg-Saric, Sakoman, & Brajsa-Zganec, 2002). Exercise and sports participation have traditionally been regarded as a means of encouraging the development of healthy habits and deterring health risk behaviors (King, Mohl, Bernard, & Vidourek, 2007;van Mechelen, Twisk, Post, Snel, & Kemper, 2000); however, the literature to date has not consistently validated the perception that physical activity/exercise/athletic participation (sport factors) are protective against SUM (McCaul, Baker, & Yardley, 2004;Moore & Werch, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Referring again to the model minority myth, these cultural stereotypes might come into play in the wrongful assumption that most Asian youth are largely high achievers, hard workers, academically motivated, and well-adjusted (Suzuki 2002). There are numerous implications in terms of having to face such a stereotype (Choi 2007), and most relevant to the current study is the fact that some adolescents may be mistakenly ignored in terms of the academic and other struggles that they actually encounter. We thus address these pressing concerns and notable gaps in the literature by explicitly focusing on both socioeconomic stress and academic outcomes among Asian youth, and identifying family obligation as a putative moderator of such stress.…”
Section: Socioeconomic Stress Among Asian American Youthmentioning
confidence: 94%
“…(Pakistani American participant) Asian and South Asian participants reported that they were perceived as innately smart, reflecting the notion of "model minority." The model minority stereotype refers to a conception of Asian Americans as an economically, professionally, and academically successful group, without consideration of the potential for individual or family distress (Choi, 2007).…”
Section: Journal Of Adolescent Researchmentioning
confidence: 99%